Is the Mangrove Beach of Serdang Berdagai Regency, North Sumatra Suitable as An Ecotourism Site? - Hasan, Uswatul; Mardiana, Siti; Hasibuan, Syahbudin (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Mangrove ecosystems have various potentials, one of which is as a tourist area. This study aims to assess the suitability of mangrove ecosystems as ecotourism areas, which can later be used as a basis for developing ecotourism on mangrove beaches in Serdang Bedagai Regency, North Sumatra Province. The research method used was survey. The research was conducted during the period July to October 2023. Mangrove observations were made using the 10 x 10 metre quadratic transect method as many as 20 pieces placed on the shoreline area towards land. thickness and density of mangroves. The results showed that there were two mangrove species, Avicennia marina and Rhizophora mucronata with a total density of 1,015 individuals per hectare (10.15 individuals per 100 mÂ²). There are 16 types of biota associated with mangrove ecosystems consisting of 3 types of bivalves, 1 type of gastropod, 6 types of fish, 3 types of crustaceans, 2 types of arthropods, and 1 type of mammal. The results of the ecotourism suitability index analysis show that this area is suitable to be used as a mangrove ecotourism location with a suitability value of 54.75%. Thus, it can be concluded that the mangrove beach is suitable to be used as an ecotourism area.